Factors Affecting Global Integration of Chinese Multinationals in Australia: A Qualitative Analysis - Fan, David; Zhu, C.; Nyland, C. (Pergamon, 2012)
This study utilizes cross-level and in-depth interviews to extend empirical and conceptual studies that have identified the factors underlying the choices made by OECD based multinational enterprises (MNEs) when determining their approach to global integration. The study examines the applicability of these factors in the context of Chinese MNEs with operations in Australia. In so doing, it pioneers the use of qualitative methods to determine which factors affect emerging market MNEs’ global integration and how these elements function and interrelate. Furthermore, the study contributes to theory-building by classifying the factors affecting global integration into organizational, industrial, and environmental groupings. The implications of this study are drawn from the data analysis and directions for future studies are advanced.